The adaptation of media companies to corporate Social responsibility standards and best practice - Campos Freire , Francisco (2022)
Organizations, economically sustainable, must serve people, inside and outside of them, to contribute from the mission mark, to his happiness. Assuming that the higher the impregnation of organizational culture, the greater degree of happiness among people of an organization are the results of an investigation that allowed linking people’s happiness, a psychosocial approach, with the implementation of organizational culture (meaning belonging and commitment). The case study was conducted in 2011/2012 on a European leader in the distribution sector.